АНАЛИЗ ПРЕДПРИНИМАТЕЛЬСКОЙ АКТИВНОСТИ В СФЕРЕ ТУРИЗМА РЕГИОНОВ КАЗАХСТАНА (Экономика: стратегия и практика)
Modern tourist business is one of the largest and fastest growing sectors of the economy. Often the tourism industry is seen as a mediator of economic and social changes in society. In addition, tourism is able to support national unification through the inflow of foreign currency, encourage cultural activities and traditional crafts, and have a significant impact on the survival of various service sectors. The tourism industry plays a significant role in creating jobs, reducing unemployment mainly due to the development of tourism entrepreneurship, able to eliminate social problems, give impetus to the development of the country and replenish the budget, leading to an increase in gross domestic product.The purpose of the work is to determine the level of development of entrepreneurial activity in the field of tourism in the regions of Kazakhstan. The study is based on the application of the main statistical methods: grouping, number of dynamics.The article analyzes tourist flows by type of tourism, the share of tourism in GDP, the number of active subjects in the field of tourism in dynamics for the last 5 years.The result of the study was the rating of the regions of Kazakhstan on the development of entrepreneurial activity in tourism, identifying factors hindering the development of entrepreneurship in tourism, proposals to increase the attractiveness of areas as tourist destinations.The field of application of the research results is the activity of subjects of the tourist industry: the Ministry of Culture and Sports, Department of tourism development, tour operators and travel agents, industry organizations, consumers.The results of the study can be used in the development of regional tourism development programs as part of the implementation of the state tourism development program until 2023.